(3eTQhY GdYeQ (B/s - (3GdadGMj, eTYd Hf YHO GdYRjRs ((3OeTb (B:s (3HjQhJ (B:s (3OGQ Gdbde ;s (3GdOGQ GdTGejI,s, 2010)
(3eTQhY GdYeQ Hg jMK GdcGJH eTYd YHO GdYRjR GdadGMj cd EfSGf eSde Edi cJGHg eTQhY MjGJg hjbhd dg (B((3GHOC cJGHI MjGJc(B) (3hHPdc jchf gPG GdcJGH gh GdNWhI GdYedjI GdJWHjbjI deTQhY GdYeQ hjbhd (B"(3GdadGMj ce fMf HMGLI Edi Cf jSCd cd EfSGf efG HfaSg gPg GdCSFdI ef CfG ? HeGPG CYQa Hjf GdfGS ? eGPG bOeJ aj JGQjN MjGJj ? Cj JGQjN cJHJ ? hCj dMXGJ YTJ ? gd CeG EVGaI MjI aj gPg GdOfjG ? Ce YHA Kbjd Ydi GdCQV ? eG gh eTQhYj GdPj YTJ dg MjGJj(B.s
(3HHdjhLQGajI (B: (3UaMI (B153.s
Keywords: (3GdESdGe hGdYed GdGLJeGYj GdJWhYjs; (3JMbjb GdPGJs